Propriedades topológicas de hiperespaços - Bryant Rosado Silva (2023)
Given a topological space, one can take the collection of subsets satisfying one or more properties and equip this collection with a topology. As such, this collection is called a hyperspace. In this dissertation, we aim to discuss a wide range of topological properties that hyperspaces can satisfy depending on the properties the base space satisfies and vice versa. This is done for the Vietoris topology as well as for the uniform topology, which we show coincide with the Hausdorff metric when the space is metric. In order to be able to do it, we review concepts of General Topology and discuss the theory of uniform spaces.